2020
DOI: 10.1177/2059700220947197
|View full text |Cite
|
Sign up to set email alerts
|

Situational factors associated with concussion in cricket identified from video analysis

Abstract: Video analysis of situational factors associated with head impacts and concussion has been completed in several sports, however has yet to be completed in cricket. This study aimed to identify situational factors associated with concussion in elite Australian male and female cricket. Match video of head impacts were coded for player position, impacting object, source of ball, location of impact, and where the ball went after impact. Head impacts were then categorised as either concussion or no concussion based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Therefore, travel into the green zone on the frontal view may in fact appear in the red zone in the sagittal view, suggesting diagnosis could be improved with access to multiple angles. This is supported by the findings of Saw et al 24 who conducted a similar exercise in Australian cricket and demonstrated that the rebound of the ball towards the source or the ball stopping dead was associated with a higher risk of concussion. Standardisation of the views and reference frame in future may assist in investigating this further.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Therefore, travel into the green zone on the frontal view may in fact appear in the red zone in the sagittal view, suggesting diagnosis could be improved with access to multiple angles. This is supported by the findings of Saw et al 24 who conducted a similar exercise in Australian cricket and demonstrated that the rebound of the ball towards the source or the ball stopping dead was associated with a higher risk of concussion. Standardisation of the views and reference frame in future may assist in investigating this further.…”
Section: Discussionsupporting
confidence: 68%
“…[21][22][23] In cricket, where the bowling line is permitted to contact the batsman who must react, impacts to the front of the helmet may result from a faster ball speed while a slower ball on a similar trajectory may prompt a player to turn their head in preparation for an impact. However, this relationship is clearly complex, as demonstrated by Saw et al, 24 who's work highlighted that impacts to the back of the helmet carried the highest positive predictive value of concussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury incidence was 24.8%8 to 28.9% 2 for fast bowlers and 5.9% 8 to 8% 2 for slow bowlers. Injury incidence for batting was 10.1% 37 to 57.9% 40 . Injury incidence for all-rounders who bowl and bat was 38.5% 8 to 41.2% 37 .…”
Section: Resultsmentioning
confidence: 96%
“…Medical-attention injuries were reported in seven studies 2,3,30,36,37,40,41 . Medical-attention injuries accounted for 100% of all injuries sustained in five studies 2,3,37,40,41 .…”
Section: Resultsmentioning
confidence: 99%